2023
DOI: 10.1097/hep.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis delta: Epidemiology to recent advances in therapeutic agents

Abstract: Hepatitis D virus (HDV) was first described in 1977 and is dependent on the presence of hepatitis B surface antigen (HBsAg) for its entry into cells and on the human host for replication. Due to the envelopment with the hepatitis B virus (HBV) envelope, early phases of HDV entry resemble HBV infection. Unlike HBV, HDV activates innate immune responses. The global prevalence of HDV is estimated to be about 5% of HBsAg positive individuals. However, recent studies have described a wide range of prevalence betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 191 publications
0
1
0
Order By: Relevance
“…It is unclear where HDV RNA is sensed as replication occurs in the nucleus but the innate immune sensors are located in the cytoplasm (Figure 1). 1 …”
Section: Lifecyclementioning
confidence: 99%
See 3 more Smart Citations
“…It is unclear where HDV RNA is sensed as replication occurs in the nucleus but the innate immune sensors are located in the cytoplasm (Figure 1). 1 …”
Section: Lifecyclementioning
confidence: 99%
“…It blocks the viral receptor on the hepatocyte and prevents new infections as well as protects naïve hepatocytes. [1] It has been approved for use in chronic HDV in Europe. [12] One study in a real-world cohort in Germany showed virologic response in 87 of the 114 patients in the study.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…HDV-infected patients have a higher risk of developing cirrhosis and hepatocellular carcinoma (HCC) as well as hepatic decompensation and increased mortality in comparison with HBV mono-infected patients [ 27 ]. Despite the severity of this disease, the underlying mechanism is still unknown and hence there is a lack of effective treatments to control HDV-induced liver damage [ 28 ]. One of the main reasons for the scarce knowledge of the molecular mechanism/s involved in the pathology of this disease is the absence of adequate animal models that resemble the main pathological features observed in HDV patients and are amenable to experimentation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%